Corrections to "Variational adaptive correlation method for flow estimation" [Jun 12 3053-3065] - Becker, Florian; Petra, Stefania; Schnörr, Christoph (IEEE transactions on image processing, 2012)
In the above paper (ibid., vol. 21, no. 6, pp. 3053-3065, Jun. 2012), several corrections requested by the authors were omitted. The IEEE regrets the error. On pp. 3058 and 3059, the algorithms were not indented corrected. They are corrected here.